Endometrial Cut Off Thickness as Predictor of Endometrial Pathology in Perimenopausal Women with Abnormal Uterine Bleeding: A Cross-Sectional Study. (4th January 2022) - Kumari, Priti; Gaikwad, Harsha S.; Nath, Banashree
Abstract : Purpose . We aim to determine the predictive value of endometrial thickness by transvaginal ultrasonography (TVS) in diagnosing endometrial pathology and to evaluate whether Doppler complements its diagnostic efficacy in perimenopausal women with abnormal uterine bleeding. Methods . This cross-sectional observational study was conducted among 70 perimenopausal women with AUB who underwent TVS measurement of endometrial thickness (ET) and Doppler flow indices followed by endometrial sampling and histopathological examination (HPE). Results . In HPE, 51 (73%) women had normal diagnosis while 19 (27%) women had neoplastic histology either benign or malignant. They were categorised into group I and group II, respectively. There was a significant difference in age (P = 0.001 ) and incidence of obesity (P = 0.01 ) between the two groups. The ETs measured in group I and group II were 7.89 ± 2.62 mm and 14.07 ± 3.96 mm, respectively, with significant difference (P < 0.001 ). A TVS-ET of 10.5 mm had the highest sensitivity and specificity of 89.5% and 86.3%, respectively, PPV of 70.68%, NPV of 95.68%, LR+ of 6.52, and LR− of 0.12. Doppler flow velocimetric study of endometrial and uterine vessels did not demonstrate a significant difference. Conclusions . Women in perimenopause with AUB should be offered to undergo endometrial sampling for histopathological examination if TVS ET ≥10.5 mm. The coexisting risk factors especially higher age (>45 years) and obesity (BMI>30) significantly escalate the chances of developing endometrial pathology.